CSR Bakti Sosial Program By Siti Khodijah Muhammadiyah Hospital, Sepanjang Branch, To Improve The Health Of Mothers And Children In The Bebekan Village - Annas, Muhammad Choirul; Hardjati, Susi (UNIVERSITAS PAKUAN, 2025)
The contribution of private companies in Sidoarjo Regency to corporate social responsibility (CSR), particularly in the field of health, is very low, causing concern among several parties. At the same time, the child mortality rate in Sidoarjo Regency is quite high, including in Bebekan Village. Therefore, private sector contributions, including those from private hospitals, are needed to help address these issues. RS Siti Khodijah Muhammadiyah Branch Sepanjang, as a private hospital, is also fulfilling this obligation, as initial observations by the researcher indicate that RS Siti Khodijah is actively involved in community-based social activities. The purpose of this study is to determine the implementation of corporate social responsibility (CSR), specifically the CSR Social Service programme by RS Siti Khodijah Muhammadiyah Branch Sepanjang to improve maternal and child health in Bebekan Village. The research method uses a qualitative descriptive approach and focuses on the programme implementation model according to Korten (1980). Data collection techniques include observation, interviews, and documentation. The research findings indicate: 1) Program, in the program focus, there is alignment between the program and the beneficiaries' needs. This is evident from the program planning, objectives, and clear budget, as well as community involvement. 2) Implementing organisation, in this focus, there is also alignment between the tasks required by the program and the capabilities of the implementing organisation. Where the division of labour and implementation guidelines carried out by the implementing organisation align with their competencies. 3) Beneficiaries, in this focus area, the programme has also been implemented effectively. This is evident from the achievement of the target, namely a reduction in child mortality rates in the Bebekan neighbourhood. The conclusion of the study is that the implementation of the CSR Bakti Sosial programme is effective and aligns with Korten's (1980) programme implementation model. Keywords: Implementation, CSR Bakti Sosial, Maternal and child health